The “complex reality” (LG, 8) of the Church in the light of the Incarnate Word: II. Analysis and Post-conciliar Reception of the Text - Derpich, Nikola (Alpha omega, 2020)
Since Reimarus certain Christologies have made formal and methodologicaldistinctions between the historical Jesus and the Christ of faith, premises that became points of departure for the “Jesus Quest” and theologies of religious pluralism that required Magisterial interventions such as Dominus Iesus. Number 8 of the Vatican II dogmatic constitution on the Church, Lumen Gentium, presents an analogy between the mystery of the Church and the mystery of the Incarnate Word, describing the Church as, like Christ, a “complex reality which coalesces from a divine and a human element.” Christological approaches that divide the Incarnate Word into the historical Jesus and the Christ of faith will necessarily lead to repercussions in ecclesiology. The goal of this inquiry is to see how the mystery of the Incarnate Word sheds light on the mystery of the Church, in the light of Lumen Gentium 8.